Pengembangan Portal Web Kemanusiaan untuk Publikasi Sosial dan Transparansi Donasi Cakra Abhipraya - Rafi Bowo Raharjo; Devara Isbani Yusuf; Edhy Poerwandono; Mesra Betty Yel (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
The development of information technology has encouraged social and humanitarian organizations to utilize web-based systems as effective and transparent information media. Cakra Abhipraya Responsif Organization still faces challenges in publishing social activities and providing centralized and easily accessible donation reports for the public and donors. Information delivered through social media or manual methods is considered insufficient to optimally build public trust. This study aims to develop a responsive web-based humanitarian portal that functions as a medium for publishing social activities and improving donation transparency at Cakra Abhipraya Responsif Organization. The research method used is a qualitative approach with data collection techniques including observation, interviews, and documentation. The system development process consists of requirement analysis, system design, implementation, and functional testing. The results indicate that the developed web portal is able to present social activity information, donation data, and transparency reports in a structured manner and is easily accessible across various devices. The implementation of this portal is expected to improve the effectiveness of social activity publication, maintain donation transparency, and increase public and donor trust in the organization.